Longterm Outcomes of Patients Undergoing Liver Transplantation for Acute‐on‐Chronic Liver Failure. Issue 12 (25th August 2020) - Sundaram, Vinay; Mahmud, Nadim; Perricone, Giovanni; Katarey, Dev; Wong, Robert J.; Karvellas, Constantine J.; Fortune, Brett E.; Rahimi, Robert S.; Maddur, Harapriya; Jou, Janice H.; Kriss, Michael; Stein, Lance L.; et al.
Abstract : Recent data have demonstrated >80% 1‐year survival probability after liver transplantation (LT) for patients with severe acute‐on‐chronic liver failure (ACLF). However, longterm outcomes and complications are still unknown for this population. Our aim was to compare longterm patient and graft survival among patients transplanted across all grades of ACLF. We analyzed the United Network for Organ Sharing database for the years 2004‐2017. Patients with ACLF were identified using the European Association for the Study of the Liver–Chronic Liver Failure criteria. Kaplan‐Meier and Cox regression methods were used to determine patient and graft survival and associated predictors of mortality in adjusted models. A total of 56, 801 patients underwent transplantation of which 31, 024 (54.6%) had no ACLF, 8757 (15.4%) had ACLF grade 1, 9039 (15.9%) had ACLF grade 2, and 7891 (14.1%) had ACLF grade 3. The 5‐year patient survival after LT was lower in the ACLF grade 3 patients compared with the other groups (67.7%; P  < 0.001), although after year 1, the percentage decrease in survival was similar among all groups. Infection was the primary cause of death among all patient groups in the first year. Infection was the primary cause of death among all patient groups in the first year. After the first year, infection was the main cause of death in patients transplanted with ACLF grade 1 (32.1%), ACLF grade 2 (33.9%), and ACLF grade 3 (37.6%), whereas malignancy was the predominant cause of death in those transplanted with no ACLF (28.5%). In conclusion, patients transplanted with ACLF grade 3 had lower 5‐year survival as compared with patients with ACLF grades 0‐2, but mortality rates were not significantly different after the first year following LT. Graft survival was excellent across all ACLF groups. Abstract : https://www.wileyhealthlearning.com/Activity/7201344/disclaimerspopup.aspx